Giongo Onomatopoeic Expressions in Doraemon Volume 3 - Vamelia Aurina Pramandhani; Anik Yulianti (Universitas Dian Nuswantoro, 2026)
This study aims to describe the forms and meanings of giongo onomatopoeia found in Doraemon manga Volume 3. This research employs a descriptive qualitative method. The data consist of giongo onomatopoeia appearing in the text and visual illustrations within manga panels. Data analysis was conducted by classifying the onomatopoeia based on their forms and interpreting their meanings according to visual and situational contexts. The results indicate that giongo onomatopoeia are predominantly in the form of single words with sound prolongation and reduplication, which function to strengthen the impression of sounds, movements, and events. Seven giongo onomatopoeia in single-word forms and three in reduplicated forms were identified. The meanings of giongo onomatopoeia are not solely determined by their lexical meanings but are also influenced by visual context within the manga panels, helping readers to imagine sounds more vividly.